NPTool: a simulation and analysis framework for low-energy nuclear physics experiments. (7th March 2016) - Matta, A; Morfouace, P; Séréville, N de; Flavigny, F; Labiche, M; Shearman, R
Abstract: The Nuclear Physics Tool (NPTool) is an open source data analysis and Monte Carlo simulation framework that has been developed for low-energy nuclear physics experiments with an emphasis on radioactive beam experiments. The NPTool offers a unified framework for designing, preparing and analyzing complex experiments employing multiple detectors, each of which may comprise some hundreds of channels. The framework has been successfully used for the analysis and simulation of experiments at facilities including GANIL, RIKEN, ALTO and TRIUMF, using both stable and radioactive beams. This paper details the NPTool philosophy together with an overview of the workflow. The framework has been benchmarked through the comparison of simulated and experimental data for a variety of detectors used in charged particle and gamma-ray spectroscopy.